Effects of nitric oxide inhalation on pulmonary gas exchange during exercise in highly trained athletes - Durand, F.; Mucci, P.; Safont, L.; Prefaut, C. (Acta Physiologica Scandinavica, 1999)
The pathophysiology of exercise-induced hypoxaemia in elite athletes is still unclear but several studies indicate that a diffusion limitation, which could be explained by an interstitial pulmonary oedema, is a major contributing factor. Stress failure would induce a haemodynamical interstitial oedema with inflammatory reaction and release of mediators like histamine. Histamine release was found to be correlated with the hypoxaemia in elite athletes. If stress failure is involved, inhalation of pulmonary vasodilatators such as nitric oxide during exercise in athletes should induce an inhibition of the histamine release and a reversal of the hypoxaemia. Nine male endurance-trained young athletes performed two randomized exercise tests: one without and the other with 15 p.p.m. of inhaled NO. Measurements of histamine release and arterial blood gas analysis were performed at rest and at 50, 75 and 100% V·O2max. At rest, inhaled NO induced a decrease in PaO2 and an increase in (Ai-a)DO2 suggesting increased perfusion of units with low V·A/V·Q·. During exercise, NO inhalation suppressed the histamine release observed without NO and induced a moderation in the decrease in PaO2 and the increase in (Ai-a)DO2 observed between 75 and 100% of V·O2max (P < 0.005). In conclusion, this study showed that NO inhalation inhibited exercise-induced histamine release in highly trained athletes, but we were unable to confirm the suppression of exercise-induced hypoxaemia (EIH). An unexpected result was that inhaled NO seemed to have a marked effect on arterial oxygenation in highly trained-athletes, by disturbing gas exchanges.